2016
DOI: 10.1021/acs.est.6b03913
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Analyses of Lead Adsorption on the (001), (110), and (012) Hematite Surfaces

Abstract: Predicting the environmental fate of lead relies on a detailed understanding of its coordination to mineral surfaces, which in turn reflects the innate reactivity of the mineral surface. In this research, we investigated fundamental dependencies in lead adsorption to hematite by coupling extended X-ray absorption fine structure (EXAFS) spectroscopy on hematite particles (10 and 50 nm) with resonant anomalous X-ray reflectivity (RAXR) to single crystals expressing the (001), (012), or (110) crystallographic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 51 publications
3
36
0
1
Order By: Relevance
“…Adsorption of arsenate on hematite surfaces also showed facet-dependence, the bridging bidentate arsenate complexes were formed on the {012} hematite facet, while the edgesharing complexes appeared on the {012} and {102} facets. 12,13 In addition, Noerpel et al 14 revealed that both outer-sphere and bidentate lead complexes were formed on the {001}, {012} and {110} hematite facets, wherein the hematite with exposed {110} and {012} facets exhibited better adsorption performance than that with {001} facets. These coordination structures commonly have a strong correlation with the surface coverage; for example, bidentate binuclear complexes appeared to have higher surface coverage than monodentate ones.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of arsenate on hematite surfaces also showed facet-dependence, the bridging bidentate arsenate complexes were formed on the {012} hematite facet, while the edgesharing complexes appeared on the {012} and {102} facets. 12,13 In addition, Noerpel et al 14 revealed that both outer-sphere and bidentate lead complexes were formed on the {001}, {012} and {110} hematite facets, wherein the hematite with exposed {110} and {012} facets exhibited better adsorption performance than that with {001} facets. These coordination structures commonly have a strong correlation with the surface coverage; for example, bidentate binuclear complexes appeared to have higher surface coverage than monodentate ones.…”
Section: Introductionmentioning
confidence: 99%
“…69,247 Noerpel et al used resonant anomalous X-ray reflectivity (RAXR) to determine the surface coverages of Pb 2+ sorbed on various hematite facets and similarly showed that the {012} and {110} facets (with higher densities of singly and triply coordinated hydroxyl groups than {001}) had a higher surface coverage of Pb 2+ per surface area. 76 The higher density of singly coordinated hydroxyl groups on the {100} surface of hematite was also shown to be responsible for the greater sorption capacity (per surface area) of humic substances compared with the {001} facet, 235 with analogous conclusions for enhanced sorption and subsequent hydrolysis of 4-nitrophenyl phosphate on the {100} vs. {001} facet of nanohematite. 238 In addition to relative differences in sorption capacities, recent research has demonstrated that different facets of nanoscale hematite also promote different complexation geometries for both inorganic and organic contaminants.…”
Section: Applicationsmentioning
confidence: 96%
“…73,74 Comparison of the reflectivity profiles suggests that the halflayer termination is the dominant termination in water but that some full-layer termination exists. 69,73,75,76 The clean {001} facet has been reported to have three different terminations: a single Fe termination, a double Fe termination, and an O termination. 77 The Fe single termination and O termination have been observed as coexisting and are variably stable depending on the oxygen partial pressure, oxidation conditions, annealing temperature, and whether the measurements are done in a dry or humid/aqueous environment.…”
Section: Atomic and Electronic Characteristics Of Nmo Facetsmentioning
confidence: 99%
See 2 more Smart Citations